Doped graphene encapsulated SnP2O7 with enhanced conversion reactions from polyanions as a versatile anode material for sodium dual-ion battery. (10th February 2021) - Wu, Qiong; Wang, Jiazhi; Wang, Heng-guo; Si, Zhenjun; Li, Chunpin; Bai, Jie
Abstract: Tin-based ternary oxides have obtained much attention for energy storage systems due to high capacity based on alloying/dealloying reactions and improved cycling performance resulted from the inactive buffer matrix. Herein, SnP2 O7 particles are encapsulated into N/P dual-doped graphene (SnP2 O7 /NPG), which is served as an universal anode material for sodium-ion batteries (SIBs) and sodium-based dual-ion batteries (SDIBs). Benefiting from the unique structure of tin-based ternary oxides and synergy effect of multicomponent, the obtained SnP2 O7 /NPG delivers a good reversible capacity of 412.9 mAh g −1 at 0.05 A g −1, superior cycling performance of 86.2 mAh g −1 at 2 A g −1 after 1000 cycles, and exceptional rate performance of 182.3 mAh g −1 at 2 A g −1 in Na + half cells. Especially, assembly of SnP2 O7 /NPG with the graphite cathode could yield a SnP2 O7 /NPG-graphite SDIBs, which shows high rate performance (up to 2 A g −1 ) and good cycling stability over 100 cycles with a capacity retention of 63.2%. Furthermore, the Na + insertion/extraction mechanism is systematically investigated using the extensive kinetics investigation. This work provides inspirations as to extending the wider application prospect of tin-based ternary oxides in energy storage systems.